Pathways to Industrial Decarbonization in Thailand Toward Net-Zero 2050 - Wangjiraniran, Weerin; Nakapreecha, Nitida; Pongthanaisawan, Jakapong (International Journal of Energy Economics and Policy, 2026)
This study develops model-based pathways for achieving net-zero greenhouse gas emissions in Thailand’s industrial sector, integrating policy foresight with quantitative energy system modeling. Using the Low Emission Analysis Platform (LEAP) framework, nine industrial subsectors were analyzed under three transition scenarios—Path of Challenge, Visionary Goal, and Balancing Growth—to assess the techno-economic feasibility of decarbonization through 2065. The model incorporates structural transformation, technology diffusion, and policy enforcement parameters to simulate future energy demand and emission trajectories. Results highlight that policy enforcement and the pace of low-carbon technology adoption are the dominant determinants of industrial emission outcomes. Under the Visionary Goal scenario, which aligns with current national policy direction, Thailand could reach net-zero emissions by 2065; however, this requires an accelerated GHG reduction rate and early deployment of high-impact technologies such as hydrogen and carbon capture, utilization, and storage (CCUS). The Balancing Growth scenario, emphasizing rapid industrial restructuring and early technology commercialization, demonstrates a potential to achieve net-zero before 2050, contingent on industrial emissions peaking between 2025–2030. Conversely, the Path of Challenge scenario—characterized by delayed technology uptake and limited policy intervention—shows that the net-zero target becomes unattainable, with cumulative emissions exceeding the allowable carbon budget by over 30 MtCO₂e. The findings underscore the need for coherent long-term industrial and energy policies that simultaneously promote innovation, strengthen institutional mechanisms such as the forthcoming Climate Change Act, and incentivize early commercialization of emerging technologies. Integrating policy ambition with targeted technology acceleration is essential for Thailand’s industrial sector to align with national and global net-zero trajectories.